Recurrent MALAT1–GLI1 oncogenic fusion and GLI1 up‐regulation define a subset of plexiform fibromyxoma. Issue 3 (20th May 2016) - Spans, Lien; Fletcher, Christopher DM; Antonescu, Cristina R; Rouquette, Alexandre; Coindre, Jean‐Michel; Sciot, Raf; Debiec‐Rychter, Maria
Abstract: Plexiform fibromyxomas are rare neoplasms, being officially recognized as a distinct entity among benign mesenchymal gastric tumours in the 2010 WHO Classification of Tumours of the Digestive System . Characteristically, these tumours have a multinodular/plexiform growth pattern, and histologically contain variably cellular areas of bland myofibroblastic‐type spindle cells embedded in an abundant myxoid matrix, rich in capillary‐type vessels. As yet, the molecular and/or genetic features of these tumours are unknown. Here we describe a recurrent translocation, t(11;12)(q11;q13), involving the long non‐coding gene metastasis‐associated lung adenocarcinoma transcript 1 ( MALAT1 ) and the gene glioma‐associated oncogene homologue 1 ( GLI1 ) in a subgroup of these tumours. The presence of the fusion transcript in our index case was confirmed using polymerase chain reaction (PCR) on genomic DNA, followed by Sanger sequencing. We showed that the truncated GLI1 protein is overexpressed and retains its capacity to transcriptionally activate its target genes. A specific FISH assay was developed to detect the novel MALAT1–GLI1 translocation in formalin‐fixed, paraffin‐embedded (FFPE) material. This resulted in the identification of two additional cases with this fusion and two cases with polysomy of the GLI1 gene. Finally, immunohistochemistry revealed that the GLI1 protein is exclusively overexpressed in those cases that harbour GLI1 /12q13 genomic alterations. In conclusion, overexpression of GLI1 through a recurrent MALAT1–GLI1 translocation or GLI1 up‐regulation delineates a pathogenically distinct subgroup of plexiform fibromyxomas with activation of the Sonic Hedgehog signalling pathway. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.